The minimum wage and Latino workers - Pia M. Orrenius; Madeline Zavodny (Institute for the Study of Labor (IZA), 2010)
Latinos comprise a large and growing share of the low-skilled labor force in the U.S. and may be disproportionately affected by minimum wage laws as a result. We compare the effects of minimum wage laws on employment and earnings among Hispanic immigrants and natives compared with non-Hispanic whites and blacks. We focus on adults who have not finished high school and on teenagers, groups likely to earn low wages. Conventional economic theory predicts that higher minimum wages lead to higher hourly earnings among people who are employed but lower employment rates. Data from the Current Population Survey during the period 1994-2007 indicate that there is a significant disemployment effect of higher minimum wages on Latino teenagers, although it is smaller for foreign- than native-born Latinos. Adult Latino immigrants' earnings are less affected by minimum wage laws than other low-education natives, and their employment rates appear to increase when the minimum wage rises. We investigate whether skill levels and undocumented status help explain these findings.
Keywords: J23; J38; J15; 330; Latinos; Hispanics; minimum wage; low-skilled; immigrants